The financial sector and economic development : the Mexican case - Bennett, Robert Lee. (Baltimore : Johns Hopkins Press, 1965)
The book outline a theory of the role of the financial sector in economic development as exemplified in the Mexico financial sector. A theory which recognizes important institutional differences between underdeveloped countries and advanced countries during the early years of their development.
Includes index.
Includes bibliographical references p. 190-196.
usc 21/9/17
Loans
Keywords: Finance; Banks and banking; Economic history; Mexico